Effect of dietary polyphenol rich grape (Vitis vinifera) seed extract supplementation on production performance, egg quality, plasma MDA, reproductive performance and faecal microbiota of golden laying hens - Abdul Hafeez; Saad Ullah; Shabana Naz; Abdulwahed Fahad Alrefaei; Rifat Ullah Khan; Samia H. Abdelrahman; Caterina Losacco; Maria Selvaggi (Journal of Applied Animal Research)
The study investigated the effects of grape seed extract (GSE) supplementation on laying hens aged 30–35 weeks. Hens were assigned to four groups: a control group with only basal diet and three experimental groups with basal diet supplemented with 250 (GSE 250), 500 (GSE 500) and 750 (GSE 750) mg/kg GSE. GSE-supplemented groups showed significantly lower feed intake in week 1 and 3 in GSE 750. No significant differences were observed in feed efficiency, egg weight, shell thickness, yolk weight, albumin weight, or Haugh Unit, suggesting GSE did not significantly impact these parameters. Egg production significantly increased in groups supplemented with 500 and 750 mg/kg GSE compared to the control group. Additionally, GSE-supplemented birds exhibited significantly lower levels of malondialdehyde (MDA), a marker of lipid peroxidation, indicating potential antioxidant effects. The study further revealed a significant increase in Lactobacillus at GSE500 and GSE 750 levels and a significant reduction in E. coli levels with GSE 750 supplementation, suggesting potential benefits on gut microbiota. In conclusion, GSE positively influenced egg production, promoted Lactobacillus growth, and reduced lipid peroxidation and E. coli populations. However, reproductive efficiency in golden laying hens was not significantly affected. These findings contribute valuable insights into the potential benefits of GSE in poultry nutrition.